About Possibility of Proton Acceleration Up To Relativistic Energies in the Neutral Layer of the Interplanetary Magnetic Field (IMF) - Khazaradze, Nodar G.; Vanishvili, George K.; Bakradze, Temur S.; Elizbarashvili, Michael A. (Journals of Georgian Geophysical Society, 2017)
The theoretical considerations concerning the acceleration of charged particles in general and, in particular, the process of acceleration of protons in neutral layer of outer space in the frames of Maxwell electro-magnetic theory are discussed briefly. A short historical overview of developments, indicating on the fact, that proton can be accelerated up to ultra-relativistic energies in the Neutral Layer of the Interplanetary Magnetic Field, which is confirmed by anomalous huge number of cosmic rays − μ mesons, in lower layers of atmosphere, as well as in deep depths of underground and underwater, which in its turn, are generated by decay of protons through the decay of π - and κ -mesons.